ChemInform Abstract: New Advances in Titanium‐Mediated Free Radical Reactions. Issue 34 (1st August 2013) - Rossi, Bianca; Prosperini, Simona; Pastori, Nadia; Clerici, Angelo; Punta, Carlo
Abstract Review: 163 refs.